Botanical Identity of Pyinkado and Irul - Bennet, S. S. R.; Bahadur, K. N. (Indian Forester, 1978)
The Identity of Xylia spp. Of the Indo-Burmese region has been in a state of confusion. It was believed that the source of the well known Burmese timber pyinkado was X. dolubriformis and that the Indian timber irul, which is slightly inferior, was obtained from X. xylocarpa. The remaining species X. kerrii was not clearly understood. A critical study of the herbarium specimens in DD revealed that besides certain other diagnostic characters, the Indian and Burmese material invariably had gland-crested and eglandulose anthers, respectively. This, along with a review or literature, led to the conclusion that while the Indian species (irul) was no doubt X. xylocarpa, the Burmese species was iafact X. kerrii and not X.dolabriformis. Further, it became obvious that X. dolabriformis was a superfluous name for X.-xylocarpa whose distribution did not extend to Burma and tbat the only speciea indigenous to Burma, which produced pyinkado, was X.kerrii. Under its supposed name X.dolabriformis, the Burmese X. kerrii has been introduced, in the past, in Dehra Dun. and the trees are doing exceedingly well, It may be worthwhile to raise it in plantations in the Sub.Himalayan tract because pyinkado is superior to irul.